Prediction of generalized anxiety disorder treatment outcomes with neurobehavioral responses to approach-avoidance conflict: a randomized clinical trial - Hannah Berg; Timothy J. McDermott; Rayus Kuplicki; Hung-Wen Yeh; Wesley K. Thompson; Ryan Smith; Elisabeth Akeman; Namik Kirlic; Ashley Clausen; Mallory Cannon; Evan White; Christopher R. Martell; et al. (Translational Psychiatry)
Abstract Treatments for generalized anxiety disorder (GAD) often aim to address maladaptive approach-avoidance behavior patterns. Approach-avoidance conflict (AAC) offers a potential framework for identifying treatment outcome predictors and informing optimization of GAD treatment. The current study examined whether pre-treatment neurobehavioral AAC indices predict symptom improvement in behavioral activation (BA) and exposure therapy (EXP) for GAD. Treatment-seeking adults meeting criteria for GAD completed a randomized clinical trial with pre-treatment blinding, conducted from 2016–2021. Participants were randomized to complete 10 manualized sessions of BA or EXP. Participants completed an AAC task during functional magnetic resonance imaging pre-treatment. Computational parameters of task behavior were derived, and neural activity was assessed during decision-making and positive and negative outcomes of decisions. Outcome measures were GAD symptoms and depressive symptoms. Of 121 participants recruited, 56 (29 BA, 27 EXP; mean age 33.0 years; 12.5% male) treatment completers were included in analyses. Greater AAC task avoidance (d = −0.28) and greater left dorsolateral prefrontal cortex activation during negative outcomes (d = −0.32), predicted greater symptom reduction across treatments. Blunted left amygdala activation to positive outcomes was associated at a trend level with favorable symptom reduction for BA but not EXP (d = −0.20). The dorsolateral prefrontal cortex may be a target for enhancing behavior therapy outcomes generally, while left amygdala activation to positive affect may be a target for enhancing outcomes for BA. These findings may inform the optimization of behavioral therapies for GAD and hold potential for transdiagnostic applications, warranting larger, longitudinal studies in clinical settings. Clinical Trials Registration: ClinicalTrials.gov NCT02807480.